KAIDAH YANG DIPERLUKAN MUFASSIR - Yusron, M. Agus (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The rules of interpretation are the most important part for someone who wants to understand the meaning of the Qur'an, so that his understanding is close to what Allah SWT wants. and the meaning of the interpreted verse does not deviate. Lately, many interpretations of the Qur'anic verses have been issued by people who do not understand the rules of interpretation, so that the interpretation is based on their own or a group's passions and interests. Whereas according to M. Quraish Shihab, the rules of interpretation are a tool that saves someone from mistakes in interpreting the verses of the Qur'an, even though they are relative, but will be safer from mistakes if the way of interpretation is in accordance with the agreed rules. The rules of interpretation include linguistic rules, such as isim nakirah, ma'rifat, dhamir, mufrad, plural, khithab bi al-ism, khithab bi al-fi'il, as-su`al, al-response, al-wujûh, an -nazhâir, and al-musytarak; stylistic rules, such as manthûq, mafhûm, mujmal, mubayyan, 'am, khâs, muthlaq, muqayyad, haqiqat, majaz, muqaddam and mu`akhkhar; exegetical rules, such as muhkam, mutasyâbih, nasikh, mansukh, sab'ah ahruf, and others. The extent of the discussion so that in this study will only discuss linguistic rules. Each rule will be detailed in its meaning and function, accompanied by examples found in the verses of the Qur'an. After the explanation of each rule, it is clear that the rules of interpretation are mandatory for someone who wants to understand the meaning of the Qur'anic verse, because the rules will lead to an understanding of the text correctly and the application of the text to the context correctly.